Chemical Compositions of Edamame Genotypes Grown in Different Locations in the US - Yu, Dajun; Lin, Tiantian; Sutton, Kemper; Lord, Nick; Carneiro, Renata; Jin, Qing; Zhang, Bo; Kuhar, Thomas; Rideout, Steven; Ross, Jeremy; Duncan, Susan; Yin, Yun; et al. (Frontiers in Sustainable Food Systems, 2021)
The consumption of edamame [Glycine max (L.) Merr.] in the US has rapidly increased due to its nutritional value and potential health benefits. In this study, 10 edamame genotypes were planted in duplicates in three different locations in the US—Whitethorne, Virginia (VA), Little Rock, Arkansas (AR), and Painter, VA. Edamame samples were harvested at the R6 stage of the bean development when beans filled 80–90% of the pod cavity. Afterward, comprehensive chemical composition analysis, including sugars, alanine, protein, oil, neutral detergent fiber (NDF), starch, ash, and moisture contents, were conducted on powdered samples using standard methods and the total sweetness was calculated based on the measured sugars and alanine contents. Significant effects of the location were observed on all chemical constituents of edamame (p < 0.05). The average performance of the genotypes was higher in Whitethorne for the contents of free sucrose (59.29 mg/g), fructose (11.42 mg/g), glucose (5.38 mg/g), raffinose (5.32 mg/g), stachyose (2.34 mg/g), total sweetness (78.63 mg/g), and starch (15.14%) when compared to Little Rock and Painter. The highest soluble alanine (2.67 mg/g), NDF (9.00%), ash (5.60%), and moisture (70.36%) contents were found on edamame planted in Little Rock while edamame planted in Painter had the highest crude protein (43.11%) and oil (20.33%) contents. Significant effects of genotype were observed on most of the chemical constituents (p < 0.05) except NDF and raffinose. Among the 10 genotypes, R13-5029 consistently had high sucrose content and total sweetness across the three locations, meanwhile it had relatively high protein and fiber contents. Overall, the results indicate that to breed better edamame genotypes in the US, both genotype and planting location should be taken into considerations.